ABCA1, apoA-I, and BTN3A1: A Legitimate Ménage à Trois in Dendritic Cells - Riganti, Chiara; Castella, Barbara; Massaia, Massimo (Frontiers in Immunology, 2018)
Human Vγ9Vδ2 T cells have the capacity to detect supra-physiological concentrations of phosphoantigens (pAgs) generated by the mevalonate (Mev) pathway of mammalian cells under specific circumstances. Isopentenyl pyrophosphate (IPP) is the prototypic pAg recognized by Vγ9Vδ2 T cells. B-cell derived tumor cells (i.e., lymphoma and myeloma cells) and dendritic cells (DCs) are privileged targets of Vγ9Vδ2 T cells because they generate significant amounts of IPP which can be boosted with zoledronic acid (ZA). ZA is the most potent aminobisphosphonate (NBP) clinically available to inhibit osteoclast activation and a very potent inhibitor of farnesyl pyrophosphate synthase in the Mev pathway. ZA-treated DCs generate and release in the supernatants picomolar IPP concentrations which are sufficient to induce the activation of Vγ9Vδ2 T cells. We have recently shown that the ATP-binding cassette transporter A1 (ABCA1) plays a major role in the extracellular release of IPP from ZA-treated DCs. This novel ABCA1 function is fine-tuned by physical interactions with IPP, apolipoprotein A-I (apoA-I), and butyrophilin-3A1 (BTN3A1). The mechanisms by which soluble IPP induces Vγ9Vδ2 T-cell activation remain to be elucidated. It is possible that soluble IPP binds to BTN3A1, apoA-I, or other unknown molecules on the cell surface of bystander cells like monocytes, NK cells, Vγ9Vδ2 T cells, or any other cell locally present. Investigating this scenario may represent a unique opportunity to further characterize the role of BTN3A1 and other molecules in the recognition of soluble IPP by Vγ9Vδ2 T cells.